2013
DOI: 10.1521/pedi_2012_26_052
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders and Outcome of Inpatient Treatment for Depression: A 1-Year Prospective Follow-Up Study

Abstract: This study examines the relationship of personality disorders (PDs) with the outcome of an inpatient treatment for depression. One hundred sixty-eight inpatients with unipolar depression (41% with PD according to SCID-II) were assessed at admission, discharge, and 1-year follow-up. Patients without as well as with PD showed a significant and comparable intake-to-discharge symptom reduction in all inventories. At posttreatment, patients with PD scored higher in self-report measures of symptom severity (Brief Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…CBASP), the comorbidity rates on both axis I and II were considerably high (Brakemeier et al, 2011). In a comparable inpatient study axis II comorbidities in patients with unipolar depression were also higher (41%), compared with our data (Unger et al, 2013). These differences (low rate of CD and lower rates of axis II comorbidity) in our study are possibly due to the inclusion and exclusion criteria.…”
Section: Discussionsupporting
confidence: 53%
“…CBASP), the comorbidity rates on both axis I and II were considerably high (Brakemeier et al, 2011). In a comparable inpatient study axis II comorbidities in patients with unipolar depression were also higher (41%), compared with our data (Unger et al, 2013). These differences (low rate of CD and lower rates of axis II comorbidity) in our study are possibly due to the inclusion and exclusion criteria.…”
Section: Discussionsupporting
confidence: 53%
“…Possibly, patients with personality disorder show lower ' openness ' as well as ' extraversion ' and therefore are less satisfi ed with complex treatment situations. In contrast to this, other studies showed no correlation between personality disorder and lower outcome of treatment (Unger et al 2013). …”
Section: Discussionmentioning
confidence: 76%
“…depression severity) between individuals with and without PD, multivariable models controlling for significant confounders are rarely used (Casey et al, 2004;Mulder, 2002). Finally, inconsistent findings could also be explained by different outcomes on self-report versus clinician-rated measures of personality pathology and depression outcome (Mulder, 2002;Stanley and Wilson, 2006;Unger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%